2005
DOI: 10.1038/sj.gt.3302479
|View full text |Cite
|
Sign up to set email alerts
|

siRNA targeting the Leader sequence of SARS-CoV inhibits virus replication

Abstract: SARS-CoV (the SARS-Associated Coronavirus) was reported as a novel virus member in the coronavirus family, which was the cause of severe acute respiratory syndrome. Coronavirus replication occurs through a unique mechanism employing Leader sequence in the transcripts when initiating transcription from the genome. Therefore, we cloned the Leader sequence from SARS-CoV(BJ01), which is identical to that identified from SARS-CoV(HKU-39849), and constructed specific siRNA targeting the Leader sequence. Using EGFP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 44 publications
3
100
3
1
Order By: Relevance
“…Those sequences start with an A, which corresponds to the transcription initiation point of the H1 promoter. As an empirical design, we preferably chose the sites with Cell Mol Neurobiol (2008) 28:887-894 889 GC/AT ratios between 30 and 60% (Li et al 2005). Also we used the selected sequences to search GenBank to confirm their specificity.…”
Section: Knockdown Of Dcf1 Expression In the Cultured Nscs By Rnaimentioning
confidence: 99%
“…Those sequences start with an A, which corresponds to the transcription initiation point of the H1 promoter. As an empirical design, we preferably chose the sites with Cell Mol Neurobiol (2008) 28:887-894 889 GC/AT ratios between 30 and 60% (Li et al 2005). Also we used the selected sequences to search GenBank to confirm their specificity.…”
Section: Knockdown Of Dcf1 Expression In the Cultured Nscs By Rnaimentioning
confidence: 99%
“…It was reported to be 10 or 100 times more potent inhibitor of SARS-CoV than IFN-∝ and IFN-β, respectively (He et al, 2004) Chloroquine A clinically approved drug for malaria was effective with an IC50 in lower µM range (Keyaerts et al, 2004). In addition to its effect through elevation of endosomal pH, chloroquine seems to interfere with terminal glycosylation of ACE2, the the receptor for SARS-CoV (Vincent et al, 2005 (Li et al, 2005a;Wu and Huang, 2005;Zhao and Qin, 2005;Tang and Li, 2008) Homology modeling also formed a basis for designing mechanism-based irreversible inhibitors of 3CLpro with an activity of wide spectrum across coronaviruses (Yang et al, 2005a). Besides, several groups have identified a number of inhibitors of 3CLpro using a variety of approaches.…”
Section: Viral Protease Inhibitorsmentioning
confidence: 99%
“…Sequence analysis showed that there was a significant homology between bat and human viruses. Interestingly, the 29-nucleotides in the ORF-8 was present in the virus of bat origin and the most variability between the two was found to be in the S1 region of spike protein, which is responsible for receptor binding (Li et al, 2005a). Findings from all such studies were put together to establish origin of SARS-CoV.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain durable and effective antiviral therapies, viral proteins that can be disabled need to be identified. Ideally, these targets should be essential factors that share conserved sequences across many www.intechopen.com different strains or even among different species of virus of the same family, so that a single target will have broad effectiveness (Das et al, 2004;Wilson & Richardson, 2005 (Jung et al, 2010;Palanichamy et al, 2010), influenza viruses A (Seth et al, 2010;Zhiqiang et al, 2010), respiratory syncytial virus (RSV) (Bitko & Barik, 2001;Bitko, et al, 2005;DeVincenzo, J.P. et al, 2010;Zamora et al, 2010), herpes simplex virus 2 (Palliser et al, 2006), West Nile virus (WNV) (Anthony et al, 2009;Ye et al, 2011), severe acute respiratory syndrome (SARS) virus (Li et al, 2005;Wu & Chan, 2006) and cytomegalovirus (CMV) (Wiebusch et al, 2004). Sereval R&D programs are currently focusing their efforts on infection diseases, HIV is one of these examples.…”
Section: Infectious Diseases 511 Virus Infectionsmentioning
confidence: 99%